Effect of Fermented Sauropus androgynus Leaves on Meat Composition, Amino Acid and Fatty Acid Compositions in Broiler Chickens - Santoso, Urip; Fenita, Yosi; Kususiyah; Bidura, I. Gusti Nyoman Gde. (Pakistan Journal of Nutrition, 2015)
The present study was conducted to evaluate the effect of fermented Sauropus androgynus leaves (SAL) on meat composition of broiler meats. One hundred and twelve broiler chicks aged 15 days were distributed to seven groups with four replicates of four broiler chicks each. One group was fed diet without fermented SAL as the control and other six groups were fed diets 2.5 or 5% Neurospora crassa fermented SAL; 2.5 or 5% EM4 fermented SAL and 2.5 or 5% Saccharomyces cerevisiae fermented SAL. It was shown that inclusion of fermented SAL significantly affected the contents of vitamin A, beta-carotene, iron, fat, cholesterol and protein in broiler meats (p